ANALYSIS CAPACITY OF POLICY RESOURCES FOR THE IMPLEMENTATION OF MOTOR VEHICLES WEIGHING IN CENTRAL JAVA - Wahyu Kresna Aji; Kismartini kismartini (Journal of Public Policy and Management Review, 2019)
The enactment of Law Number 23 Year 2014 concerning Regional Government has provided various kinds of impacts or consequences that must be had from the existence of this policy. One of the important and interesting things affected is the withdrawal of regional government affairs or authority by the central government, namely in terms of supervision and control of cargo transport on the road through Minister of Transportation No. 134 of 2015 concerning the Implementation of Motor Vehicle Weighing on Roads. The purpose of this study was to determine the condition of the sources of policy and analyze the impact resulting from the policy after the withdrawal of authority to carry out the weighing of motor vehicles in Central Java.This research is a type of qualitative research, with a descriptive approach.The results of this study indicate that the capacity of policy sources for the implementation of motor vehiclesweighing in Central Java has not been fully fulfilled and that is not ready to support the implementation of policies.This can be seen from several indications, including the lack of capacity of staff or implementing personnel, information capacity which not optimal, and the capacity of infrastructure facilities that are still inadequate.There is only one indicator that has been fulfilled well, namely the capacity of authority. While the impact resulting from the policy of withdrawing the authority to carry out the weighing of motorized vehicles in Central Java includes the individual impacts of implementing personnel, organizational impacts, and the impact on policy objects and the social system. The reccomendation from this research is to expect related stakeholders to immediately improve the condition of the capacity of policy resources that are still inadequate and pay attention to the negative impact of the vehicle weighing policy in Central Java